Momordica charantia var. Muricata L.: need to conserve and promote its cultivation in Jammu province (J&K) (Funded Work) - MEHNAZ BANO; GEETA SHARMA (International Journal of Pharma and Bio Sciences, 2017)
Momordica charantia L., a major cucurbit of economic importance, is represented by two varieties viz. cultivated var. charantia and wild var. muricata. Both these varieties resemble each other in overall morphology except that the smaller vines of var. muricata bear small sized leaves, flowers and fruits which have delicate flavour and taste as well as more nutritious components than those found in var. charantia. Besides, the two varieties correspond with each other in having most of the pollen mother cells with 22 chromosomes which associated as 11 bivalents, with a few cells having 20-24 chromosomes. Cytomorphological similarities in the two varieties which are cross-compatible indicate that attempts can be made to transfer desirable traits of var. muricata viz. drought tolerance and resistance against fruit fly into variety charantia by crossing experiments. Despite its importance, var. muricata is grown to limited extent in India and is found at few locations in the wild. In some states as Tamil Nadu, this variety is reported to be threatened. During present surveys, small and fragmented wild populations of var. muricata have been spotted at Mansar and Purmandal in district Samba and Palli, Domel and R.S. Pura in district Jammu of Jammu Province. At none of these areas, the variety was cultivated on large scale for commercial purpose. Scarce distribution and limited cultivation of this variety in Jammu Province seems to be due to the competition faced by it from large fruit bearing var. charantia, habitat loss and fragmentation and increased dependence of farming communities on locally available vegetables. In view of these limitations, various suggestions for the conservation of this variety and promotion of its cultivation in Jammu Province have been put forth.